Development of the Recognisable Logo Design Guideline for Startup Brands (International Journal of Scientific Research and Management (IJSRM), 2019)
A logo is one of the basic components in a corporate identity or brand identity. It is the graphic representation of what an organisation is. A logo would manage to evoke the consumers’ memories. In this paper, Recognisable Logo Design Specification Guideline (RLDSG) is introduced as a process to establish the recognisable logo design that is incorporated with consumers’ emotions evaluation through the logo design perceptions for startup bramds. The RLDSG is a design guideline attempt to establish Recognisable Logo Design (RLD) towards the contribution to sustainability and successful brand logo perceptions. The investigation was conducted involving an existing brand logo design from Pos Malaysia to elaborate a logo criteria and recognisable factors of the logo. Logo design from Pos Malaysia showed that the entire element were significant to reach the recognisable logo design requirement. The verification signified from this process increases the ability of graphic designers and marketers to introduce a new logo based on design requirements and preferences.